Surface morphology of soybean, pea, whey protein isolates, and their dried gels - Polumbryk, Maksim; Shestel, Olena; Yatsenko, Olga; Yushchenko (Gonchar), Natalia; Bandura (Kuzmyk), Uliana (My University, 2019)
This study proved that SEM is a promising technique which helps to choose componentsin the composition of stabilizer dependently on the product type. It was found that theincreased amount of milk resulted in the development of 3D structure formation, as expected. Pea isolate was characterized by the great ability to the crosslinking between macromolecules of proteins. Therefore it cannot be used in the butter pastes, but may be especially useful in the cheese manufacturing. This study is limited by a low number of studied proteins isolates.Further study on larger number of proteins isolates is necessary to investigate role ofhydration level on the 3D- structure development.
Keywords: morphology; морфологія; proteins; білки; whey; сироватка; кафедра технології молока і молочних продуктів; кафедра технології ресторанної і аюрведичної продукції; кафедра готельно-ресторанної справи